2019
DOI: 10.3390/su11174622
|View full text |Cite
|
Sign up to set email alerts
|

Employees’ Perceptions of Training and Sustainability of Human Resource

Abstract: Employees’ perceptions of training are one of the keys to sustainability in human resources. Based on data from a survey conducted in Shanghai and nine other large cities, this study explores employees’ perceptions of training and tries to identify what factors influence their perceptions. The results show that employees do not attach enough value to vocational training. Urban registration, higher education, and management positions correspond with higher valuation of training, but length of service has a nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Measuring training outcomes in increments of payments supports the PAV concept (Breuer & Kampkötter, 2013). Company-specific management training is also drawing attention from the perspective of sustainability (Lee et al, 2019). Furthermore, Singh et al (2019) empirically shows that sustainable training leads to a company's competitive advantage.…”
Section: Personnel-adjusted Added Valuementioning
confidence: 82%
“…Measuring training outcomes in increments of payments supports the PAV concept (Breuer & Kampkötter, 2013). Company-specific management training is also drawing attention from the perspective of sustainability (Lee et al, 2019). Furthermore, Singh et al (2019) empirically shows that sustainable training leads to a company's competitive advantage.…”
Section: Personnel-adjusted Added Valuementioning
confidence: 82%
“…Lee et al reported "Employees' Perceptions of Training and Sustainability of Human Resource" [7]. This study explores employees' perceptions of training and tries to identify what factors influence their perceptions.…”
Section: Gu Et Al Reported "Empirical Examination Of Intention To Comentioning
confidence: 99%
“…Lin [11] discussed the critical role of comprehensive employee development in achieving corporate sustainability and introduced an innovative mechanism for motivating all-around improvement, including capability enhancement and ideological coaching. Lee [12] investigated strategies to bolster employee skills, focusing on training effectiveness. Lin [13], drawing on the principle of resource scarcity, advocated for a shift in organizational focus from addressing weaknesses to accentuating strengths, facilitating superior performance at both individual and organizational levels.…”
Section: Introductionmentioning
confidence: 99%